Sistem Numeralia Bahasa-Bahasa Daerah di Papua - Ratna Mala Sukma (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Global cultural was change quickly, include of its Ianguage component, the refleksion and evaluated for vernacular life become of vital importance. The reality showed  that the symptom of life and efficacy of effort vernacular conservancy which is one vernacularly is other different of each other. There was vernacular which enough take care of, but also there are some which less be paid attention.The vernacular Ianguages in Papua have characteristic, its means every Ianguage have the differences by other Ianguage. The characteristics can concerning sound system, system of word forming, system of forming of other system or sentence. One of the unique vernacular in Papua that seldom be found was numbering system and the way of counting.This matter that make the researcher to collect and compile the vernacular system numeralia anthology in Papua, the aim of this result to audiolingual erudite article in system numeralia which exist in Papua which have been observed.Based on system of numeralia of Ianguage Papua which have been conducted, there are five of numeralia system that exists in Papua. There are: 1).language of Dani Barat have cardinal number from one until thirty one. 2).language of  Ekagi have cardinal number from one until sixty .3).language of  Gresi have cardinal number from one until thirty. 4).language of kayu pulau have cardinal number from one until five 5).language of Namblong have cardinal number from one until one hundred.